Effects of Dietary Corn Malt-Sactic Mixed Concentrate with Rice Straw and Corn Husk on Rumen Fermentation, Nutrient Digestibility, Blood Metabolites and Growth Performance in Growing Beef Heifers - Boarapa, Ratchanee; Chaiwon, Suthathip; Kuha, Kecha; Sintala, Kitsanathon; Wachirapakorn , Chalong; Wongnen, Chantira; Srakaew , Wuttikorn (Trends in Sciences, 2023)
The enhancement of protein content in grains is interesting because starch is the main energy component used in beef cattle feeds. Corn malt-sactic is a modified corn grain with increase protein content and improve digestibility through the process of malt germination and microbial fermentation. Therefore, the effects of feeding malt-sactic from corn grain as a high protein energy source in diet were investigated on rumen fermentation, nutrient digestibility, blood metabolites, and growth performance in beef heifers. Sixteen of 1-year-old Brahman crossbred growing beef heifers with an initial weight of 220 ± 24.5 kg were randomly assigned into 4 different rations according to completely randomized design (CRD). Experimental treatments were corn grain or corn malt-sactic mixed concentrates with roughage sources as follow, T1; corn grain mixed concentrate with corn husk, T2; con grain mixed concentrate with rice straw, T3; malt-sactic mixed concentrate with corn husk, and T4; corn malt-sactic mixed concentrate with rice straw. The results showed that total feed intake and digestibility of dry matter, crude protein, NDF and ADF were significantly higher in the heifers fed corn malt-sactic mixed concentrate diet than corn mixed concentrate diet (p < 0.05). Ruminal pH post-feeding, blood urea nitrogen, and blood glucose were not different among treatments (p > 0.05). Body weight gain and average daily gain were significantly higher (p < 0.05), while feed conversion ratio was lower in corn malt-sactic mixed concentrate diet as compared with corn mixed concentrate diet (p < 0.05). The source of roughage did not affect rumen fermentation, nutrient digestibility, blood metabolites, or growth performance (p > 0.05). Results indicated that using corn malt-sactic as an ingredient in beef heifer diets can improve digestibility and growth performance. HIGHLIGHTS The addition of corn malt-sactic enhances both malt germination and microbial fermentation. Incorporating a corn malt-sactic mixed concentrate diet boosts heifers' feed intake and improves digestibility. Utilizing a corn malt-sactic mixed concentrate diet leads to improved Average Daily Gain (ADG) and Feed Conversion Ratio (FCR) in heifers. GRAPHICAL ABSTRACT